Nutrition literacy status and its association with adherence to the Mediterranean diet, anthropometric parameters and lifestyle behaviours among early adolescents - Gamze Yurtdaş Depboylu; Gülşah Kaner; Melisa Süer; Mesude Kanyılmaz; Duygu Alpan (Cambridge University Press, 2023)
Abstract Objective: To evaluate nutrition literacy status and its association with adherence to the Mediterranean diet (MD), anthropometric parameters and lifestyle behaviours among early adolescents. Design: This is a cross-sectional study. Nutrition literacy was evaluated using the 'Adolescent Nutrition Literacy Scale'. Dietary intake was assessed by 24-h food recall. The 'Mediterranean Diet Quality Index' was used to evaluate adolescents' adherence to the MD. Physical activity was assessed using the International Physical Activity Questionnaire (IPAQ). Body weight, height, waist, hip and neck circumference were measured. Setting: Four secondary schools in İzmir, Türkiye Participants: The study included 1074 secondary school students. Results: Adolescents' nutrition literacy was at a moderate level. Nutrition literacy scores were significantly lower in those who skip main meals. Adolescents with high nutrition literacy had higher intakes of fibre, protein, protein, Ca, K, Mg, P, vitamin C, folate and Fe intake than those with low and moderate nutrition literacy (P < 0·05). According to IPAQ, active adolescents had higher nutrition literacy scores than inactive adolescents. There was no significant difference in BMI and anthropometric measurements of the adolescents according to their nutrition literacy level. Linear regression analysis showed that each unit increase in nutrition literacy increased adherence to the MD by 0·286 points (β = 0·286) and decreased total screen time by 0·182 points (β = -0·182). Conclusions: These findings showed that nutrition literacy among early adolescents was not optimal, and a higher nutrition literacy score was significantly associated with higher MD adherence, and healthy eating habits and lifestyle behaviours.